Experimental study of a diesel engine heat pump in heating mode for domestic retrofit application. (5th April 2016) - Shah, N.N.; Huang, M.J.; Hewitt, N.J.
Highlights: Diesel engine heat pump test set-up was developed <10 kW heating capacity. R134a based water-to-water source heat pump was designed considering waste heat recovery. Influence of engine speed and evaporation temperature was evaluated. DEHP optimisation to match heating demand and comparison with conventional heating system. DEHP application potential by reducing primary energy consumption and CO2 emission. Abstract: An engine driven heat pump (ENHP) can provide better efficiency compared to electric heat pump (EHP) considering primary energy consumption. The present work aimed to find suitability of diesel engine heat pump as a domestic retrofit application for off or weak gas/electricity network area. For this work, water-to-water heat pump test facility was developed which consisted heat pump, diesel engine and heat recovery arrangements. The system performance was evaluated for 65 °C flow temperature from condenser at three different engine speeds (1600, 2000 and 2400 rpm) and four evaporator water inlet temperatures (0, 5, 10 and 15 °C). The system performance was evaluated by heating capacity, isentropic efficiency, coolant heat recovery, exhaust gas heat recovery and PER. Performance analyses showed that heat recovery contributed 33% in total heat output where heat recovery was in a range of 1.7 to 3.7 kW. PER varied in the range of 0.9 to 1.4 showing good potential in terms of 35–65% primary energy saving and 23–42% CO2 emissions reduction compared to conventional systems. DEHP optimisation showed ability to meet water flow temperature requirement of 65–73 °C by speed variations and heat recovery providing good potential to meet heating demand during winter and summer periods in retrofit settings.